PEMEROLEHAN KALIMAT ANAK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK FKIP UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study discusses the acquisition of sentence children aged 4-5 years based on the mode in kindergarten FKIP University of Riau ie, declarative sentence, imperative sentence, interrogative sentences and sentences ekslamatif. This study used a qualitative approach and descriptive method that aims to describe the acquisition of sentence children aged 4-5 years. The subjects totaled nine children consisting of five boys and four girls. This study uses a data type that is rooted in oral speech to school children in kindergarten FKIP University of Riau. Data obtained using the technique of recording and record, then classified based on the type of sentence, and then formulated into a knot. Based on data analysis, the conclusion is obtained that children aged 4-5 years in kindergarten FKIP Riau University has been able to use declarative sentences, 4-5 year-olds are already able to use the imperative sentence, imperative sentence is a sentence that has been obtained (1) imperative taktransitif, (2) an imperative transitive, (3) smooth imperative, (4) the imperative demand, (5) imperatives solicitation and expectations, (6) imperative prohibition, (7) the imperative of omission. Children aged 4-5 years have been able to use the interrogative sentence, phrase introgatif who have obtained it form a sentence; (1) interrogatory requesting recognition of a yes or no or yes or not, (2) the requested interrogatory answers regarding one of the elements (what, who, where, how, when), (3) the requested interrogatory answers in the form of reasons, ( 4) interrogatory requesting an answer in the form of an opinion, (5) presenting interrogative, and children aged 4-5 years has gained ekslamatif sentences to express his feelings.Keywords: acquisition sentences, mode, children 4-5 years old.